Targeting Gram-negative Superbugs with Polymyxins: From Lab-Bench to Bedside - Vinall, Phil (MD Conference Express, 2012)
Extensively drug resistant Gram-negative superbugs Pseudomonas aeruginosa, Acinetobacter baumannii, and Klebsiella pneumoniae present a global medical challenge due to their resistance to almost all current antibiotics, and no new antibiotics will be available for many years to come. Frequently, the only active antibiotics currently in use are colistin (polymyxin E) and polymyxin B. This article presents an overview of how polymyxins kill Gram-negative superbugs and how resistance develops.